Waqf Behavior During The Covid-19 Pandemic - Harahap, Darwis; Arif, Muhammad; Farizal, Nando; Nauli, Mutiara (Jurnal Iqtisaduna, 2020)
Waqf is one of the instruments that are highly expected, even productive and the results can help the economy, education, and even the welfare of the community during the current COVID-19 pandemic. This is in stark contrast to the results of accumulating waqf in Indonesia which are still low compared to their potential. This study aims to look at the behavior of waqf in donating one's assets during the COVID-19 pandemic. This study uses descriptive quantitative analysis using the Theory of Planned Behavior approach. The data used in this study are primary data obtained through giving questionnaires to respondents. The hypothesis of this study was tested using Partial Least Square (PLS) analysis. The results of this study indicate that the variables of subjective norms, behavioral control, and religious commitment have an influence on waqf behavior during the COVID-19 pandemic. Meanwhile, attitudes and knowledge variables have no influence on waqf behavior. The implication of this research can be input for campuses, institutions or waqf management foundations to be able to increase waqf literacy which can support the interest of waqif in giving waqf in a pandemic or in the future.